2015
DOI: 10.1164/rccm.201409-1582oc
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Mites Induce Proliferation of Severe Asthmatic Smooth Muscle Cells via an Epithelium-Dependent Pathway

Abstract: This work demonstrates the selective role of HDM on BSM remodeling in patients with severe asthma and points out different therapeutic targets at epithelial and smooth muscle levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 42 publications
2
56
1
Order By: Relevance
“…One study has suggested leukotriene receptor antagonists possess growth inhibitory effects in animal models (23), yet no human studies have provided evidence for an antiremodeling effect of leukotriene receptor antagonists (21,28). Interestingly, a recent in vitro study by Trian et al, using a human bronchial epithelial and smooth muscle cell (obtained from severe persistent asthmatic subjects) coculture model, demonstrated that epithelium-generated paracrine factors, including leukotrienes, regulate ASM proliferation that could be inhibited by pretreating cells with the leukotriene receptor antagonist montelukast (53). Additional in vivo studies are needed to further ascertain the effect of leukotriene receptor antagonists on airway remodeling in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…One study has suggested leukotriene receptor antagonists possess growth inhibitory effects in animal models (23), yet no human studies have provided evidence for an antiremodeling effect of leukotriene receptor antagonists (21,28). Interestingly, a recent in vitro study by Trian et al, using a human bronchial epithelial and smooth muscle cell (obtained from severe persistent asthmatic subjects) coculture model, demonstrated that epithelium-generated paracrine factors, including leukotrienes, regulate ASM proliferation that could be inhibited by pretreating cells with the leukotriene receptor antagonist montelukast (53). Additional in vivo studies are needed to further ascertain the effect of leukotriene receptor antagonists on airway remodeling in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…BSMCs were further isolated from bronchial specimens as described previously 15. Patient characteristics are presented in online supplementary table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The use of single allergen immunotherapy is often the concern regarding oral immunotherapy; however, the targeting of treatment with dust mite allergen makes sense given that this is known to be the most frequent indoor allergen associated with asthma worldwide. In fact, recent laboratory data demonstrated that house dust mite exposure selectively increased the proliferation of bronchial smooth muscle in patients with severe asthma [40]. It is expected that future research will continue to develop oral immunotherapy with a particular focus on dust mites.…”
Section: New Treatments To Disrupt the Allergen–asthma Associationmentioning
confidence: 99%